WITHIN-SESSION RELIABILITY AND VALIDITY OF OVERHAND BALL THROW TEST TO EVALUATE POWER ABILITY IN JUNIOR TENNIS PLAYERS - Károly DOBOS; Péter János TÓTH (Cluj University Press, 2021)
Introduction: Coaches should be able to estimate successfully different physical attributes of junior tennis player's performance such as power, in order to monitor players' progress and to design the most appropriate training program. However, this process requires reliable and valid field tests. Objective: Aim of this study was to examine absolute and relative reliability of overhand ball throw (OBT) test within testing session and to investigate its validity. Methods: 257 Hungarian junior boy and girl tennis players (aged 11-17) separated into four groups, performed OBT and serve speed (SS) tests of standardised protocol. Results: Dependent sample t-test revealed no significant (p= 0.31-57>0.05) difference between test and retest sample means within testing session and magnitude of effect size (dz=0.1-0.5) were trivial for all groups. Furthermore, all groups had low typical percentage error (CV= 3-4 %), and standard error of measurement values was consistently low (SEM= 0.12-0.18). Within test-retest consistency illustrated strong relative reliability (ICC= 0.98-0.99). Moreover, significantly large to very large positive correlations were found between OBT and SS (r= 0.57-0.81; p˂0.01) tests. The coefficient of determination indicated that OBT explained 32-65% of the SS for groups. Conclusions: These findings suggest that absolute and relative reliability of OBT test is high within testing session and validity of OBT test is acceptable for measuring power ability of flat serve execution in junior tennis players.